Financial Behavior to Enhance Student Engagement in Cooperative Enterprise - Martono, Adi; Fadillah, Fadillah (Dinasti Publisher, 2026)
The dwindling number of active cooperatives in Indonesia suggests the urgency of a revival effort, such as increasing involvement through better integration of youth in cooperative business operations. As one of the important groups, university students should be considered in sustaining and reviving the development of the cooperative system. This study investigates the factors affecting the engagement of students in cooperatives by identifying the effects of financial literacy, benefits perception, trust in the cooperative management system, and social norms, as well as the mediating effect of information exposure and the moderating effect of risk propensity. To achieve its objectives, this study used a quantitative explanatory research method through Partial Least Squares Structural Equation Modelling (SEM-PLS). Data were obtained from 404 undergraduate students using an online questionnaire. The results showed that the level of students' cooperation engagement was significantly affected by social norms and benefit perception. It means that social influence and the recognition of benefits should receive special attention in fostering participation in cooperative activities. Besides, financial literacy only has a direct impact on students' information exposure and does not significantly affect students' engagement. Moreover, trust and risk propensity have no significant effect, nor does the moderation of risk propensity.